Multiscale distribution patterns of pelagic rafts of sargasso (Sargassum spp.) in the Mexican Caribbean (2014–2020) - Uribe-Martínez, Abigail; Berriel-Bueno, Diana; Chávez, Valeria; Cuevas, Eduardo; Almeida, Karla L.; Fontes, Jassiel V. H.; van Tussenbroek, Brigitta I.; Mariño-Tapia, Ismael; Liceaga-Correa, Maria de los Ángeles; Ojeda, Elena; Castañeda-Ramírez, D. Gerardo; Silva, Rodolfo (Frontiers in Marine Science, 2022)
As the biomass of pelagic Sargassum spp. increased across the North Atlantic equatorial recirculation region from 2011 onwards, massive rafts of sargasso appeared in the Western Caribbean in 2015, 2018, 2019, and 2020. These events raised concerns regarding their negative consequences on the environment, local income, and human wellbeing. As adequate monitoring and analysis tools are needed for designing in-water and on-beach control strategies to reduce potential negative impacts, more robust and spatially explicit information is needed in order to improve sargasso management and focus restoration efforts. In this paper, we offer a spatiotemporal multiscale description of sargasso distribution and dynamics for 2014–2020 in the Mexican Caribbean: (1) for the entire region (millions of km2); (2) at the local scale (thousands of km2) evaluating the dynamics inside the reef lagoon at Puerto Morelos, Mexico; and finally, (3) specific beach observations (hundreds of km2) derived from data on beach cleaning volumes. Fifteen areas in the Mexican Caribbean, with different sargasso dispersions and on-shore accumulations, were evaluated. The areas around Tulum, Solidaridad, and Puerto Morelos have the most extreme and most frequent episodes but also exhibited the greatest seasonal variability. Extreme sargasso presence can occur in the Western Caribbean in any season, albeit with increasing coverage and recurrence in the summer. Images from a coastal video monitoring station at Puerto Morelos showed that massive sargasso beaching was associated with low energy conditions (Hs< 0.25 m, wind speed<4 m/s, neap tide), while non-accumulation of sargasso on the beach occurred under high energy conditions (Hs >0.4 m, wind speed = 8 m/s, spring tide). Time-series analyses of sargasso beaching showed different periods of historic maximum sargasso coverage over July–October 2018 and others in January–February 2019. Wind and wave regimes influenced sargasso in distinct ways, depending on the coastal section, probably related to coastline morphology, oceanic regime, or the extent of the continental platform. This work presents the longest systematic time series (2014-2020) of high resolution satellite detected sargasso in Mexico. Spatial and temporal patterns are proposed as fundamental steps for managing sargasso accumulations.